Proposal for standardized ultrasound analysis of the salivary glands: Part 1 submandibular gland - Hoffman, Henry T.; Koch, Michael; Witt, Robert Lee; Ryan, William R.; Zenk, Johannes; Katz, Philippe; Rahmati, Rahmatullah; Rassekh, Christopher; Donato, Francisco; McCulloch, Timothy M.; Joshi, Arjun S.; Chang, Jolie Lien; et al. (Laryngoscope Investigative Otolaryngology, 2024)
Objectives: The Salivary Gland Committee of the American Academy of Otolaryngology-Head and Neck Surgery seeks to standardize terminology and technique for ultrasonograpy used in the evaluation and treatment of salivary gland disorders. Methods: Development of expert opinion obtained through interaction with international practitioners representing multiple specialties. This committee work includes a comprehensive literature review with presentation of case examples to propose a standardized protocol for the language used in ultrasound salivary gland assessment. Results: A multiple segment proposal is initiated with this focus on the submandibular gland. We provide a concise rationale for recommended descriptive language highlighted by a more extensive supplement that includes an extensive literature review with additional case examples. Conclusion: Recommendations are provided to improve consistency both in performing and reporting submandibular gland ultrasound.
CRIS-Team Scopus Importer:2024-03-01
Keywords: anatomic subsites; color doppler; salivary glands; shear wave elastography; submandibular; ultrasound